Pendidikan Dan Pengetahuan Ibu Tentang Gizi Berhubungan Dengan Status Gizi Balita - Dwi Ertiana; Shafira Berliana Zain (STIKES Karya Husada Kediri, 2023)
Mother's level of education and knowledge are factors that affect the nutritional status of children under five. Malnutrition is the cause of the high mortality rate in children under five and reduces the quality of life, disrupts growth and development. The purpose of this study was to analyze the relationship between mother's education and mother's knowledge about the nutritional status of children under five at the Sedap Malam Posyandu, Pakunden Village, Sukorejo District, Blitar City. The research design used analytic with the type ofdesign cross sectional. The population in this study were all mothers and toddlers at the Sedap Malam Posyandu, Pakunden Village with 31 respondents as research subjects. The independent variable is mother's education and mother's knowledge about toddler nutrition and the dependent variable is the nutritional status of toddlers. Collecting data with questionnaires, observation sheets, KMS, Stepping Scales. Univariate data analysis using frequency distribution and bivariate using Spearman rank. The results showed that the education level of the majority of mothers in senior high school was 15 mothers (48.4%), the majority of mothers had high knowledge of 17 mothers (54.8%), and the nutritional status of the majority of toddlers was good as many as 21 children (67.7%). The results of the Spearman rank test of maternal education with nutritional status of toddlers 0.012 <0.005 with a correlation value of 0.445. While the results of the mother's knowledge test with the nutritional status of toddlers 0.018 <0.05 with a moderate correlation value of 0.421, so Ho is rejected and Ha is accepted. The conclusion in this study is that there is a relationship between mother's education and level of knowledge with the nutritional status of children under five. Education and knowledge of mothers of children under five affect changes in behavior and attitudes related to nutrition given to toddlers, these problems can be overcome by providing health promotion through collaboration with health workers, because it will greatly affect the quality of human resources in future generations.